PERBANDINGAN PENAMBAHAN BABY OIL DAN AIR SOFTLENS PADA EYEBROW GEL TERHADAP HASIL AKHIR PAES YOGYA PUTRI - Amanda Enggar Valentina; Usodoningtyas, Sri; Fernanda, M.A. Hanny Ferry; Pritasari, Octaverina Kecvara (Jurnal Tata Rias, 2025)
An innovation was carried out by mixing eyebrow gel with two types of solvents, namely baby oil and contact lens solution, in order to find the best mixing ratio based on aesthetic evaluation and the durability of paes. The author aims to explore the Yogya Putri bridal paes makeup, particularly the use of alternative materials to replace traditional pidih, which is easily smudged when scratched. Data analysis was conducted using the Kruskal-Wallis test as an alternative to ANOVA for non-parametric data. The test results showed a significant difference between ratios (p < 0.05). Ratio 1 demonstrated the highest performance in almost all aspects, except in durability, where Ratio 3 was superior. Overall, Ratio 1 is recommended as the best ratio as it provides an aesthetically pleasing appearance of paes, is comfortable to apply, and has good adhesiveness. These findings confirm that modern cosmetics such as eyebrow gel can be applied in traditional makeup, as long as the formulation and application techniques are appropriate. Future research is suggested to include physico-chemical stability testing, ingredient safety on the skin, and durability testing under various environmental conditions. Keywords: Paes, Yogya Putri, Eyebrow gel, Baby oil, Contact Lens Solution.